Logic-based perspectives on query reformulation over restricted interfaces - Benedikt, M (Association for Computing Machinery, 2018)
We overview recent developments on query reformulation over a restricted interface, in the presence of integrity constraints. We overview an approach to the problem via reduction to query containment with constraints, where the reduction makes use of interpolation algorithms from logic. We first present the approach in the context of reformulating one query as another query using a fixed set of tables. We then generalize to reformulation of a query as a plan over a set of access methods.